Validation of a HPLC-DAD–ESI/MSn method for caffeoylquinic acids separation, quantification and identification in medicinal Helichrysum species from Macaronesia - Gouveia, Sandra C. (2012)
The caffeoylquinic acids (CQA) found in Helichrysum species from Madeira Archipelago were identified and quantified. The HPLC-DAD–ESI/MSn method applied was developed and validated showing a good repeatability with recovery values ≥96%. The use of a RP-C18 with a small internal diameter (Ø 3.0 mm) and an acidic mobile phase (acetonitrile and water with 0.1% (v/v) of formic acid) enabled the separation of all compounds within a 30 min analysis. A good resolution between 1,5-O-diCQA and 3,5-O-diCQA isomers, usually hard to separate, was also accomplished. Dicaffeoylquinic acids isomers were the major components among the quantified hydroxycinnamic acids. 1,5-O-diCQA, 3,5-O-diCQA and 5-O-CQA were the compounds found in higher amounts for the different species. The distinct uses of these plants described in the local folk medicine can be related to the phenolic composition.